Influence of the Adsorbate Structure and Surface Barrier at Micropores : The Adsorption on Columnar-Structured Gold Electrodes of Pyridine from Aqueous Perchlorate Ion-Containing Solutions - Gómez, M. M. (1997)
The electroadsorption on columnar Au electrodes (substrate) of pyridine from x M pyridine + 0.1 M HClO4 and x M pyridine + 0.1 M KClO4 aqueous solutions (10-3 e x e 10-2), at constant potential and 298 K, was studied using voltammetry, chronocoulometry, and ac impedance combined with scanning tunneling microscopy to characterize the substrate topography. For a constant pyridine concentration (c), the degree of surface coverage by pyridine adsorbate (θ) diminished as R was increased. The θ vs c plots, irrespective of R, were interpreted by a Frumkin adsorption isotherm including a constant standard adsorption free energy. The evaluation of adsorption isotherms reflects the existence of an excluded volume effect, which can be related to a barrier effect due to adsorbates at nanometer size pore entrances.